Selfcare Management In Diabetic - Ardhiles Wahyu Kurniawan; Heny Nurmayunita; Risa Putri Rahmadani (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Diabetes Mellitus (DM) is a disease characterized by increased blood glucose levels and is a disease that needs attention. Diabetes mellitus cannot be cured, but it can be controlled by controlling blood sugar levels to prevent complications from occurring. These complications can be minimized with self-care management . This research aims to find out description self - care management on patient diabetes mellitus in the Kendalsari Community Health Center area, Malang City.This type of research is descriptive with an approach. The research was conducted in the Kendalsari Public Health Center area, Malang City on March 2023 with a sample size of 44 people. How to take samples is non-probability sampling that is purposive sampling. Tool measure that used is questionnaire Summary of Diabetes Self-Care Activities (SDSCA). Data collection is presented in the form of a frequency distribution table. Based on results self-care research patient management almost half of diabetes is in the good category amount 17 people (38.63%), the majority on enough category amount 27 people (61.37). DM patients are expected to improve self-care management behavior to improve health status and prevent further complications.